Bushmeat, wet markets, and the risks of pandemics: Exploring the nexus through systematic review of scientific disclosures. Issue 124 (October 2021) - Peros, Colin Scott; Dasgupta, Rajarshi; Kumar, Pankaj; Johnson, Brian Alan
Highlights: A systematic review was conducted to understand the disease surveillance efforts within the bushmeat trade and wet markets. Reported bushmeat studies were biased towards Africa, with data gaps in Asia and South America. Of the 58 species of bushmeat investigated, 48 species were found to host one or more pathogens. Perceived health risks are low among traders and consumers. The need to address the nexus between bushmeat, wet markets, and disease control should be emphasized. Abstract: The novel coronavirus (SARS-CoV-2) is the third coronavirus this century to threaten human health, killing more than two million people globally. Like previous coronaviruses, SARS-CoV-2 is suspected to have wildlife origins and was possibly transmitted to humans via wet markets selling bushmeat ( aka harvested wild meat). Thus, an interdisciplinary framework is vital to address the nexus between bushmeat, wet markets, and disease. We reviewed the contemporary scientific literature to: (1) assess disease surveillance efforts within the bushmeat trade and wet markets globally by compiling zoonotic health risks based on primarily serological examinations; and (2) gauge perceptions of health risks associated with bushmeat and wet markets. Of the 58 species of bushmeat investigated across 15 countries in the 52 articles that we analyzed, one or more pathogens (totaling 60 genera of pathogens) were reported in 48 species, while no zoonotic pathogens were reported in 10 species based on serology. Burden of disease data was nearly absent from the articles resulting from our Scopus search, and therefore was not included in our analyses. We also found that perceived health risks associated with bushmeat was low, though we could not perform statistical analyses due to the lack of quantitative perception-based studies. After screening the literature, our results showed that the global distribution of reported bushmeat studies were biased towards Africa, revealing data deficiencies across Asia and South America despite the prevalence of the bushmeat trade across the Global South. Studies targeting implications of the bushmeat trade on human health can help address these data deficiencies across Asia and South America. We further illustrate the need to address the nexus between bushmeat, wet markets, and disease to help prevent future outbreaks of zoonotic diseases under the previously proposed "One Health Framework", which integrates human, animal, and environmental health. By tackling these three pillars, we discuss the current policy gaps and recommend suitable measures to prevent future disease outbreaks.